The effect of season on response of growing-finishing pigs to dietary fat levels - G L Allee; G R Stoner; M E Johnston; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1987)
This experiment was conducted to examine the influence of season on the response of finishing pigs to practical levels of fat addition. A total of 378 pigs (average initial weight per trial ranging from 83 to 98 pounds) were utilized in four finishing trials conducted during time frames approximating the 4 seasons of the year. Groups of pigs were taken off trial as they reached market weight (230 pounds). There was no season x fat level interaction for any of the criteria measured. Therefore, it is concluded that season has essentially no effect on fat level response. Fat addition influenced average daily gain (ADG), resulting in significant (P<.05) linear and quadratic effects. Average daily feed intake (ADFI) and feed efficiency (F /G) responded linearly (P<.05) to fat additions to the finishing diet. The ADG and ADFI responses to fat additions were not affected by season. However, F/G was influenced by season. The pigs were more feed efficient during the warmer seasons of the year.; Swine Day, Manhattan, KS, November 19, 1987
Keywords: Swine day; 1987; Kansas Agricultural Experiment Station contribution; no. 88-125-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 528; Swine; Growing-finishing pigs; Fat levels